THE ROAD TO RESEARCH PRODUCTIVITY: CAPABILITY, MOTIVATION, AND CHALLENGES IN CONDUCTING RESEARCH AMONG MASTER TEACHERS - Pablo, Jennewyne V; Collantes, Leila M; Pentang, Jupeth; Gaboy, Regidor G; Astrero, Emily T (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
The evolving educational landscape and the growing concerns in the educational sector prompted master science teachers to conduct, disseminate, and utilize research. This study described the research capabilities, motivations, and challenges master science teachers face and examined the relationships among these variables. Data were gathered from 113 master science teachers in nine participating public schools in the Division of Nueva Ecija, Philippines, through a questionnaire. Results revealed that although they can identify research problems, choose approaches, and analyze data, they are challenged in managing research obligations, particularly regarding time and funds. Motivated to enhance teaching methods and support the educational community, master science teachers overcome these obstacles to show great degrees of professional and personal desire to participate in research. To help master science teachers create a stronger research culture, this study underlines the importance of institutional assistance, including improved access to research funds and professional development opportunities. There is a need to explore more factors to improve the research culture and contributions to education by Philippine master science teachers.